Soil-forming processes and ESP concept in modern soil classifications - M. I. Gerasimova (Бюллетень Почвенного института им. В.В. Докучаева, 2015)
Identification and systematic of elementary soil-forming processes (ESP) is an important contribution of I.P. Gerasimov to pedology. The ESP concept was derived of the ideas of S.S.Neustruyev, and is now implemented and advanced by the pupils and followers of I.P. Gerasimov; it was comprehensively discussed in the monograph of the same name published in 1992. In his paper of 1975, I.P. Gerasimov described 13 ESP sensu stricto , categorized them, and proposed to apply them for the diagnostics of most well-known soils of the USSR. For them, he proposed “process and profile codes” that were later modified into “profile formulas” and efficiently introduced into the Russian system of soil classification. An analysis of Russian and world soil classification systems in terms of the role of soil-forming processes in them has shown that they cannot be used as differentiating criteria (with few exceptions) although their knowledge contributes to better understanding of soils and soil properties. Nevertheless, soil-forming processes, similar to the elementary ones in their essence, perform an important function of controlling the choice, definitions and discriminative boundaries of diagnostic tools (horizons, properties and materials). In accordance with the traditions of the Dokuchaev School much attention is paid to soil-forming processes in the Russian system: processes serve as criteria to specify the genetic features identifying the subtypes.